Health technology assessment infrastructure for emirates health services: a phased framework - Hannawi, Suad; Ojeil, Rita; Alnaqbi, Abdalla; Almarshoodi, Khadija; Alzaaroni, Essam; Alzaaroni, Abdulaziz; Almoheiri, Noor; Al-Salmi, Sondos; Hannawi, Haifa; Al-Salmi, Maria; Al-Hemyari, Sabaa Saleh (Frontiers in Health Services, 2025)
This policy brief presents a structured, phased framework to establish Health Technology Assessment (HTA) within Emirates Health Services (EHS), promoting evidence-based decision-making and optimizing healthcare delivery. The model emphasizes capacity building, stakeholder engagement, and transparency to enhance patient outcomes and ensure financial sustainability. It follows four phases: Phase 0 (strategy alignment, stakeholder mapping), Phase 1 (budget impact and disease burden analysis), Phase 2 (managed entry agreements, multi-criteria decision analysis), and Phase 3 (full HTA adoption with performance metrics). Key methodologies include budget impact modeling, cost-effectiveness, and cost-utility analysis. Evidence is drawn from registries, clinical databases, and pharmacoeconomic studies. The framework offers a scalable and sustainable roadmap for HTA in the UAE, supporting efficient technology integration, optimal resource allocation, and alignment with national priorities. However, the framework's successful implementation will depend on the availability of high-quality local data, sustained stakeholder engagement, and supportive regulatory mechanisms. Potential challenges such as resource constraints, fragmented governance, and variability in HTA maturity across the region highlight the need for flexibility and adaptive strategies.